Superior CO2 adsorption from waste coffee ground derived carbons. Issue 37 (26th March 2015) - Travis, Will; Gadipelli, Srinivas; Guo, Zhengxiao
Abstract : Utilising waste from spent coffee grounds KOH activated highly microporous carbons with surface areas of 2785 m 2 g −1 and micropore volumes of 0.793 cm 3 g −1 were synthesised that are capable of uptake capacities near 3 mmol g −1 at 50 °C and 1 bar. Abstract : Utilising the hugely abundant waste from spent coffee grounds (CGs), KOH activated highly microporous carbons with surface areas of 2785 m 2 g −1 and micropore volumes of 0.793 cm 3 g −1 were synthesised that are capable of uptake capacities near 3 mmol g −1 at 50 °C and 1 bar. Importantly such uptake capacities are achieved though the material's superior microporous character and without doping within the carbon matrix, thereby ensuring facile regeneration with a binding enthalpy of only 26 kJ mol −1 and therefore being capable of energy unintensive cycleable adsorption processes. Furthermore, excellent tunability of pore-size is demonstrated from narrow micropores through to narrow mesopores, enabling optimised adsorption over a range of pressures.